Curcumin Electropolymerization to Graphite Modification for Pb2+ Electrochemical Sensing - Marwati, Siti; Prodjosantoso, Anti Kolonial; Padmaningrum, Regina Tutik; Wiraputri, Luthfia (Universitas Negeri Yogyakarta, 2024)
Curcumin is an organic ligand that can be electrocatalytic. Curcumin can be coated on graphite electrodes to produce electrodes modified with curcumin (GPC). Curcumin acts as a ligand and forms complex compounds with metals. The modification process was carried out by electropolymerization. The electrochemical method characterized the electroactive area, electron transfer, and interaction between the electrode and Pb2+ metal ions. Functional groups and surface morphology were characterized using FTIR and SEM. Validation of analytical methods including linear range, sensitivity, limit of detection, limit of quantitation, precision, and accuracy. The interaction of the GPC electrode with Pb2+ follows the electrochemical adsorption process. The GPC electrode can identify the presence of Pb2+ metal ions with a range of 3.01-70.03 µM and 181-919.2 µM. The results of the analytical method validation include linear ranges of 3.125-67.400 µM and 179.334-919.5 µM; sensitivity of 3.3605 µA/µM; limit of detection of 6.07 µM; limit of quantitation of 18.39 µM; precision of 0.93%; and accuracy of 99%.